2019
DOI: 10.1002/jsfa.9703
|View full text |Cite
|
Sign up to set email alerts
|

SpoilagePseudomonasbiofilm withEscherichia coliprotection in fish meat at 5 °C

Abstract: BACKGROUND Pseudomonas are part of the indigenous microbiota of different foods, where they gradually cause spoilage. In fish meat, Pseudomonas fragi and Pseudomonas psychrophila have been identified as important spoilers. The initial aim of this study was to investigate the physiological characteristics, adhesion, and biofilm of P. fragi and P. psychrophila under temperatures related to the fish‐processing industry. The further aim was to define the problem of increased growth of pathogenic bacteria in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…Despite commonly reported improved antimicrobial activity at low temperatures, it was found that for Pseudomonas cold temperature can even increase its resistance to antimicrobials . Therefore, it is assumed that this difference was not seen due to the marked psychrotrophic nature of these bacteria …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Despite commonly reported improved antimicrobial activity at low temperatures, it was found that for Pseudomonas cold temperature can even increase its resistance to antimicrobials . Therefore, it is assumed that this difference was not seen due to the marked psychrotrophic nature of these bacteria …”
Section: Discussionmentioning
confidence: 96%
“…Taking into account good hygienic practice and integration of additional processing steps, microbiological quality of common carp meat can be improved . Pseudomonas and Shewanella are two important spoilage microorganisms in common carp, which are resistant or poorly sensitive to natural additives used in in vitro antimicrobial studies, or applied to various foods . In our study, we evaluated both genera in vitro and in situ in terms of reducing their growth and spoilage potential by adding rosemary extract, buffered vinegar and their combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, molecular methods have contributed a lot to an incomplete phenotypic description of important groups of freshwater fish spoilage bacteria (Zhang, Li, Li, Liu, & Luo, 2015). Furthermore, knowledge about spoilage prevention by the steps of fish processing (Sterniša et al, 2016;Sterniša et al, 2018), microbial interactions (Sterniša, Klančnik, & Smole Možina, 2019) and/or new packaging materials and processes has improved a lot in recent years (Yu et al, 2019;Yu, Li, Xu, Jiang, & Xia, 2017). However, not all the preservation and packaging methods have been evaluated for freshwater fish (Sterniša et al, 2016).…”
Section: Seafood Spoilagementioning
confidence: 99%